Kwalifikacja wydatków remontowych na środki trwałe w świetle orzecznictwa sądowego - Janczyk-Strzała, Elżbieta (The Qualification of Fixed Assets Reparation Expenses in the Light of NSA Verdicts, 2005)
The above article has been dedicated to the roles which NSA verdicts play in the field of fixed assets reparation expenses.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 266-270